IMPLEMENTATION OF LIFE SKILLS THROUGH CHARACTER VALUES IN TK PRESTASI GLOBAL - Sayekti, Siskha Putri (Proceeding International Seminar of Islamic Studies, 2023)
This study aims to describe the implementation of character value-based life skills education for 4-7 year olds at TK Prestasi Global. The implementation in question concerns planning, implementation of life skills education, learning, evaluation or assessment, supporting and inhibiting factors, and solutions to overcome them. The type of research used is a descriptive qualitative approach. The subjects of this research were Kindergarten A, Kindergarten B, teachers, and principals. Data collection techniques used interviews, documentation, and observation. The data that has been collected is then analyzed and reduced according to interactive techniques using the Miles and Huberman model, namely from data reduction, data presentation, and conclusion drawing. Data were tested for validity using triangulation of methods and sources. Based on the results of the study, it can be concluded that: 1) the cultivation of life skill values based on character values in TK Prestasi Global is implemented with three stages, namely planning, implementation, and assessment; 2) the values of discipline, honesty and mutual cooperation that have been instilled and successfully achieved; 3) supporting factors; curriculum that contains discipline, honesty and mutual cooperation materials; cooperation with stakeholders such as teachers, communities, facilities and infrastructure; methods; media; habituation and sustainability at school and at home; 4) inhibiting factors: children's characteristics and abilities are different; children are still in the stage of easily changing attitudes; habituation at home and school is different; the level of family education; and the large number of students makes the focus of teacher attention uneven; and 5) How to overcome the problem by implementing life skills based on character values with parent-teacher cooperation or mutual consultation.